Pengaruh Supeltas Terhadap Tingkat Pelayanan Simpang Jalan Trans Kalimantan-Komplek Griya Permata - Hawinuti, Riska (Jurnal Teknik Sipil, 2018)
The appearanced of the peoples called “Supeltas" (Sukarelawan Pengatur lalulintas=Traffic Regulatory Volunteers) occurs along with the increasing number of queue vehicles that will turn towards the road. Supeltas itself is persons (not official from the government) who manage traffic flow expecting voluntari giffts from people passing through the road. Often, these activities broke the road rules and exacerbate existing congestion. The purpose of this study was to compare the performance of unsignalizes intersections between the existing and non-existent of "Supeltas" it self. The requirement data needed are the primary data in the form of geometric data, traffic conditions, traffic and environmental conditions data, and secondary data in the form of population and location map. Traffic data collection is done using manual calculation for 2 periods on Tuesday, Wednesday and Thursday at 06.30-08.00 in the morning, noon 12.00-14.00 and afternoon at 16.30-18.30 WITA for each condition of rush hours. The calculation refers to MKJI 1997. The calculation results obtained by the degree of saturation (DS) without the "Supeltas" amounting to 1,816 and with the provision "Supeltas" of 1,525, this DS value exceeds the IHMC ( Indonesian Highway Manual Capacity) previsions 0,75. It can be concluded that the existence of "Supeltas" made a positive impact to reduce the number of DS where it decreased 16.02%.